ENT300 Giftaholics / Nurul Farhana Suria... [et al.] - Suria, Nurul Farhana; Tompell, Aviefieorennia; Ali Hassan, Bazielah; Abdul Rahim, Syafiqa Amira (2012)
There are few types of business entities. Giftaholics is a partnership business consists of four members. In this form of business, a person forms a partnership with one or more persons to carry out a business with a view to make profits. Our company’s serves both products and services to our customer. Giftaholics is a business that provides their customer with ready-made door gifts and goodie bags. Our company’s specialty is that we provide few selections in packages that is entirely different from others. For instance, in our Winter package, we provide Cotton Candy Bar as a bonus for our customer and in our Summer package, we provide Castle Tube House. Besides, in our Spring and Autumn package, we provide Cupcake Mini Station and Chocolate Fountain Delight for our customer respectively. This is our specialty compare to others where we prepare a special activity with every package that we have.